Interferensi Bahasa Ibu sebagai Tantangan Penggunaan Bahasa Indonesia Baku oleh Mahasiswa Universitas Negeri Padang - Chamelia Deres; Sheila Ivana Khalishah; Syahrul Ramadhan; Norhaliza binti Jamaluddin; Elfia Sukma (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This study examines the challenges faced by students at Universitas Negeri Padang in using standard Indonesian, with a focus on mother tongue interference within a sociolinguistic context. The aim of this research is to identify the types of interference that occur and their impact on the ability to communicate in proper Indonesian. The method used is a qualitative approach, with data collected through online questionnaires (Google Form) distributed to students from various majors. The findings indicate that mother tongue interference, particularly in the aspects of morphology and syntax, significantly affects the use of standard Indonesian among students. The conclusion of this study highlights the importance of sociolinguistic awareness in enhancing students' understanding of proper language use, as well as the need for more effective language training programs to support their communication skills in academic settings.